Emulsifying properties of minimally processed Chlamydomonas reinhardtii microalgae ingredients - Julia Baumgartner; Li-Hsuan Lin; Silvan Sgier; Oliver Bolleter; Naomi Arita-Merino; Peter Fischer; Alexander Mathys (Food Research International, 2026)

Using gas exchange measurements to monitor growth, energy expenditure, and body composition of black soldier fly larvae (Hermetia illucens) on diets varying in protein-to-carbohydrate ratio - Maja L. Schøn; Kim Jensen; Mattias Schow-Madsen; Moritz Gold; Alexander Mathys; Toke M. Schou; Ida E. Berggreen; Jan V. Nørgaard; Johannes Overgaard (Journal of Insect Physiology, 2026)

More efficient iron enrichment in heterotrophic Auxenochlorella protothecoides by nitrogen source manipulation - Byron Perez; Yanmeng Yang; Daniel Roxby; Samuel Steffen; Fengzheng Gao; Fabian Abiusi; Ferdinand von Meyenn; Jongyoon Han; Iris Haberkorn; Alexander Mathys (Bioresource Technology, 2026)

The potential of lipid droplets from the microalga Chlamydomonas reinhardtii as natural emulsions - Julia Baumgartner; Naomi Arita-Merino; Nina Schwager; Daniel Spahn; Mirella Ambrosioni; Sascha Thaler; Milad Radiom; Samy Boulos; Joseph Dumpler; Peter Fischer; Alexander Mathys (Food Hydrocolloids, 2026)

Iron bioaccessibility assessment and bioaccumulation enrichment in microalgae under different production conditions - Fengzheng Gao; Nina Lamprecht; Ute Stern; Fabian Abiusi; Christophe Zeder; Ferdinand von Meyenn; Alexander Mathys (Bioresource Technology, 2026)

A parametric LCA platform for modelling environmental impacts in plant protein processing: Application to pea, soy, and wheat protein isolates and concentrates - Armin Siegrist; Joseph Dumpler; Jing Huo; Ashley Green; Paride Azzari; Joachim Baumann; Moritz Goessler; Stephan Pfister; Alexander Mathys (Sustainable Production and Consumption, 2026)

Influence of processing on protein quality and environmental impact assessment of soy-based meat analogues - Laila Hammer; Corina Sägesser; Armin Siegrist; Mario Arcari; Moritz Goessler; Pornpimol Scheuchzer; Moritz Müller; Christoph Denkel; Joseph Dumpler; Alexander Mathys; Lotti Egger; Reto Portmann; et al. (Food Research International, 2025)

Comparison of lipid droplet extraction from cell wall-deficient Chlamydomonas reinhardtii with pulsed electric fields or osmotic shock - Julia Baumgartner; Sing Teng Chua; Maylin Blunier; Fengzheng Gao; Naomi Arita-Merino; Fabian Abiusi; Lorraine Archer; Krzysztof Cybulski; Alison G. Smith; Michael H-P Studer; Alexander Mathys (Bioresource Technology, 2025)

Micro- and nanoplastic size affects uptake and digestive tract region residence time in black soldier fly larvae during food waste bioconversion - Moritz Gold; Siebe Lievens; Jeroen De Smet; Daniela A. Peguero; Christelle Planche; Christopher Whitshaw; Andreas Scheidegger; Denise M. Mitrano; Alexander Mathys; Mik Van Der Borght (Waste Management, 2025)

Reversible electropermeabilization of Auxenochlorella protothecoides microalgae: tracking mass transfer and membrane resealing dynamics induced by pulsed electric fields - Byron Perez; Nicola Weber; Iris Haberkorn; Alexander Mathys (Algal Research, 2025)

Strategies to overcome challenges in upcycling industrial side-streams into microalgae-based foods: Auxenochlorella protothecoides as a case study - Alcine MZ Chan; Vivian JH Hau; Iris Haberkorn; Alexander Mathys; Shao-Quan Liu (Current Opinion in Food Science, 2025)

Microfiltration of microalgae biomolecules: Impact of pulsed electric fields and high-pressure homogenization on single-cell protein recovery and membrane fouling - Byron Perez; Zhao Li; Iris Haberkorn; Joseph Dumpler; Alexander Mathys; Peter Desmond (Algal Research, 2025)

Enhancing scalability and consistency in pulsed electric field processing of microalgae: Integrating single-cell suspension rheology and multiphysics simulation - Byron Perez; Paride Azzari; Reto Koller; Iris Haberkorn; Peter Fischer; Alexander Mathys (Journal of Food Engineering, 2025)

Application of a shear cell for the simulation of extrusion to test the structurability of raw materials - Corina Sägesser; Thomas Mair; Andre Braun; Joseph Dumpler; Peter Fischer; Alexander Mathys (Food Hydrocolloids, 2025)

Comparing the nutritional value and prices of meat and milk substitutes with their animal-based benchmarks across six European countries - Armin Siegrist; Ashley Green; Fabienne Michel; Alexander Mathys (Food Research International, 2024)

Soy whey and brewer’s spent grain hydrolysates wholly replace conventional medium for microalgae growth: Process performance and economic considerations - Mei Zhi Alcine Chan; Vivian Jing Han Hau; Byron Perez; Iris Haberkorn; Alexander Mathys; Shao-Quan Liu (Bioresource Technology, 2024)

Structurability of microalgae, soy and pea protein for extruded high-moisture meat analogues - Corina Sägesser; Johanna Meta Kallfelz; Samy Boulos; Joseph Dumpler; Lukas Böcker; Thomas Mair; Laura Nyström; Alexander Mathys (Food Hydrocolloids, 2024)

In situ studies of plant-based meat analog texturization - Tong Guan; Corina Sägesser; Roman Villiger; Lisa Zychowski; Joachim Kohlbrecher; Joseph Dumpler; Alexander Mathys; Patrick Rühs; Peter Fischer; Olga Matsarskaia (Food Hydrocolloids, 2024)

Preservation of agri-food byproducts by acidification and fermentation in black soldier fly larvae bioconversion - Giacomo Alciatore; Daniela A. Peguero; Moritz Gold; Christian Zurbrügg; Mutian Niu; Franco Bargetze; Alexander Mathys (Waste Management, 2024)

Characterization of high-pressure-treated Bacillus subtilis spore populations using flow cytometry — Shedding light on spore superdormancy at 550 MPa - Rosa Heydenreich; Alessia I. Delbrück; Christina Peternell; Clément Trunet; Alexander Mathys (International Journal of Food Microbiology, 2024)

Enhancing protein extraction from heterotrophic Auxenochlorella protothecoides microalgae through emerging cell disruption technologies combined with incubation - Byron Perez; Carole Zermatten; Iris Haberkorn; Alexander Mathys (Bioresource Technology, 2024)

Physical pretreatment of three biowastes to improve black soldier fly larvae bioconversion efficiency - Daniela A. Peguero; Moritz Gold; Laura Velasquez; Mutian Niu; Christian Zurbrügg; Alexander Mathys (Waste Management, 2024)

A novel approach for the protein determination in food-relevant microalgae - Corina Sägesser; Johanna M. Kallfelz; Samy Boulos; Laila Hammer; Lukas Böcker; Reto Portmann; Laura Nyström; Alexander Mathys (Bioresource Technology, 2023)

Post-high-pressure temperature and time — Overlooked parameters in high pressure treatment of bacterial spores - Rosa Heydenreich; Alessia I. Delbrück; Alexander Mathys (International Journal of Food Microbiology, 2023)

A proposed framework to develop nutrient profiling algorithms for assessments of sustainable food: the metrics and their assumptions matter - Ashley Green; Thomas Nemecek; Alexander Mathys (The International Journal of Life Cycle Assessment, 2023)
Purpose To holistically assess the sustainability of our global and local food systems, we need methods that combine environmental and nutritional/health dimensions. One option is nutritional life cycle assessment in which a nutrient or health metric is incorporated into standard environmental life cycle assessment. Measuring nutritional and environmental outcomes in tandem can help elucidate new results that can aid farmers, policymakers, industry, and consumers in transitioning to a food system that is more beneficial for our planet and our health. However, the development of nutrient profiling metrics is still ongoing; thus, we develop and test, with case studies, the “points of differentiation” framework to guide the use of these algorithms in sustainability analyses. Methods For each of these “points” in the framework, we provide the current state-of-the-art based on the literature and then offer new insights and recommendations for their use; we do this for different food levels (i.e., production systems, food items, and diets/food supply). We provide an explicit framework for nutrient adequacy metrics, while discussing the framework’s relevance to nutrient diversity and quality metrics. We also test the “points” in this framework using case studies that examine select foods representative of a diet. Results Based on our review, the “points” in this framework to consider include capping, weighting, energy standardization, across-the-board versus group-specific, dietary- and/or context-specific, validation, disqualifying nutrients (e.g., saturated fat), reference amount, processing quality, selection of nutrients/ingredients, interpretation, and data quality. Based on changes in nutrient density scores and rankings, Spearman rank correlations, and Wilcoxon signed rank p -values, the “points” that have the largest effect are energy standardization, dietary specificities when assessing nutrient indices in isolation, as well as capping and disqualifying nutrients, depending on how these are applied. We hope our proposed “points of differentiation” framework can provide new insights into this quickly evolving space by offering structure to improve standardization and transparency. Conclusion The framework provides recommendations for select “points;” nevertheless, there are still many open areas in nutritional life cycle assessment, including food functionality (e.g., processing effects, interaction factors, and bioavailability) and methodological questions related to the use of disqualifying nutrients and interpretation. Moreover, future work should focus on the role of “points” with respect to validation and differences within food groups.

Recent findings on environmental sustainability and conversion efficiency of waste-to-protein pathways - Armin Siegrist; Ashley Green; Moritz Gold; Alexander Mathys (Current Opinion in Green and Sustainable Chemistry, 2023)

Evaluation of ammonia pretreatment of four fibrous biowastes and its effect on black soldier fly larvae rearing performance - Daniela A. Peguero; Moritz Gold; Andrea Endara; Mutian Niu; Christian Zurbrügg; Alexander Mathys (Waste Management, 2023)

Experimental and simulation-based investigation of the interplay between factor gradients following pulsed electric field treatments triggering whey protein aggregation - Robert D. Axelrod; Julia Baumgartner; Michael Beyrer; Alexander Mathys (Journal of Food Engineering, 2023)

Amino acid profile and protein bioaccessibility of two Galdieria sulphuraria strains cultivated autotrophically and mixotrophically in pilot-scale photobioreactors - Greta Canelli; Fabian Abiusi; Albert Vidal Garcia; Stefano Canziani; Alexander Mathys (Innovative Food Science & Emerging Technologies, 2023)

Arthrospira platensis protein isolate for stabilization of fluid interfaces: Effect of physicochemical conditions and comparison to animal-based proteins - Pascal Bertsch; Lukas Böcker; Ann-Sophie Palm; Jotam Bergfreund; Peter Fischer; Alexander Mathys (Food Hydrocolloids, 2023)

Spatio‐Temporal Differentiation of Life Cycle Assessment Results for Average Perennial Crop Farm: A Case Study of Peruvian Cocoa Progression and Deforestation Issues - Giancarlo Raschio; Sergiy Smetana; Christian Contreras; Volker Heinz; Alexander Mathys (Journal of Industrial Ecology, 2018)
Summary The application of spatially and temporally explicit information to increase result precision is gaining momentum in Life Cycle Assessment (LCA) studies. It is vital for the assessment of environmental impact of perennial crops with non‐productive years, grown in combination with shade crops. Available studies rely on differentiated life cycle inventory data for the inputs in LCA or application of adapted impact assessment methodologies. This study uses the identification of greenhouse gas emissions (GHG) hotspots (statistically significant clusters of farms with either high or low GHG emission values) estimated from average LCA results and assesses a relative deforestation risk in such hotspots. A total of 1892 farms in the Tocache province of San Martin region of Peru were evaluated between the year 2008 and 2010. Combination of average LCA results with farm size, age and deforestation progression allowed for the identification of areas and farms with a high relative risk of environmental impacts and potential deforestation. It was estimated that farms belonging to high‐GHG emission hotspots were twice more likely to expand their agricultural frontier and cause deforestation than farms in low‐GHG emission hotspots. Combining LCA with geo‐information systems and geostatistics is a viable path to explore the differentiation of assessment results, which might lead to faster, more accurate, and resource‐efficient ways to tackle environmental impacts while also accounting for important environmental impacts such as deforestation. Further research on the application of suggested approaches with other perennial crops and other geographical areas is needed.

Meat alternatives: life cycle assessment of most known meat substitutes - Sergiy Smetana; Alexander Mathys; Achim Knoch; Volker Heinz (The International Journal of Life Cycle Assessment, 2015)